Gambaran Tingkat Pengetahuan Tentang Cuci Tangan Pada Mahasiswa Keperawatan - Sulistyowati, Arlina Dhian; Pitaloka, Agnes Rahma (Yayasan Jompa Research and Development, 2024)
In the healthcare industry, maintaining hand hygiene through good handwashing is crucial because it can stop the spread of germs and lower the risk of nosocomial infections and hospital acquired diseases. (HAIs). Hand washing is a crucial infection prevention measure.The purpose of this study is to ascertain Muhammadiyah University Klaten D III Nursing students' degree of handwashing knowledge. This study is quantitative and descriptive in nature. Technique Purposive sampling combined with a non-probability sampling strategy was used to obtain data. There are 53 responders in the research sample.Students were given a questionnaire to complete for this study. Univariate analysis was used for the analysis. The characteristics of the students who participated in this study have an average age of 19 years and are predominantly female respondents, with 47 respondents (88.7%). This research shows that students' knowledge level regarding handwashing is categorized as good for 33 respondents (62.3%), sufficient for 14 respondents (26.4%), and poor for 6 respondents (11.3%). The conclusion of this study is that the level of knowledge about handwashing among DIII Nursing students at Muhammadiyah University Klaten is categorized as good.